A Drumbeat for Tougher Sanctions. - Oswald, Rachel (CQ Magazine, 2017)
The article discusses the political relations between U.S. and Russia focusing on the bipartisan and U.S. sanctions on Russia for computer hacking ahead of U.S. presidential elections and for its military campaign with Syria.